ANALYSIS OF DETERMINING INPATIENT RATES AND THEIR RELATIONSHIP TO MINIMUM SERVICE STANDARDS (SPM) IN REGIONAL GENERAL HOSPITALS (Case Study at Budhi Asih Regional Hospital) - Mirza Kusumawati; Arni Karina; Kumba Digdowiseiso (SEAN Institute, 2023)
The aim of this research is to analyze the difference in the basic price applied by Budhi Asih Regional Hospital with the basic price produced using Activity Based Costing and analyze the minimum service standards at the hospital. The method used in this research is a qualitative method. The data used from the hospital only includes data for 2018. The benefit of this research is to increase knowledge and insight regarding the comparative application of inpatient rates at Budhi Asih Regional Hospital with Activity Based Costing and its relation to Minimum Service Standards for hospital inpatient care in determining inpatient rates. For hospitals, it is hoped that this research can provide an alternative way to calculate inpatient service rates using Activity Based Costing. The results of this study show that the rates for inpatient services using Activity Based Costing when compared with the rates at Budhi Asih Regional Hospital provide smaller results. The minimum hospital service standards illustrate that the ideal indicators are in calculating BTO, TOI, GDR, and NDR. Meanwhile, the non-ideal indicators are in the Av.LOS and BOR calculations.